Learning and signal copying facilitate communication among bird species - Wheatcroft, David (The Royal Society, 2013)
Signals relevant to different sets of receivers in different contexts create a conflict for signal design. A classic example is vocal alarm signals, often used both during intraspecific and interspecific interactions. How can signals alert individuals from a variety of other species in some contexts, while also maintaining efficient communication among conspecifics? We studied heterospecific responses to avian alarm signals that drive the formation of anti-predator groups but are also used during intraspecific interactions. In three species-rich communities in the western Himalayas, alarm signals vary drastically across species. We show that, independently of differences in their calls, birds respond strongly to the alarm signals of other species with which they co-occur and much more weakly to those of species with which they do not co-occur. These results suggest that previous exposure and learning maintain heterospecific responses in the face of widespread signal divergence. At an area where only two species regularly interact, one species' calls incorporate the call of the other. We demonstrate experimentally that signal copying allows strong responses even without previous exposure and suggest that such hybrid calls may be especially favoured when pairwise interactions between species are strong.